An unusual C-6-C-6 '' linked flavonoid from Miconia cabucu (Melastomataceae) - Rodrigues, Juliana; Rinaldo, Daniel; dos Santos, Lourdes Campaner; Vilegas, Wagner [UNESP] (Elsevier B.V., 2007)
Chromatographic fractionation of the methanolic extract from the leaves of Miconia cabucu Hoehne (Melastomataceae) afforded the first example of a C-6-C-6 linked flavone dimer, 5-hydroxy-4',7-dimethoxyflavone-(6-C-6)-5-hydroxy-3 4',7-trimethoxyflavone as well as the known compounds, quercetin- 3-O-alpha-L- rhamnopyranosyl-(2 -> 1)-O-beta-D-xylopyranoside, quercetin-3-O-alpha-L-rhamnopyranoside, myricetin-3-O-alpha-L-rhamnopyranoside, quercetin-3-O-beta-D-glucopyranoside, kaempferol -3-O-beta-D-(6-coumaroyl) -glucopyranoside and gallic acid. Their chemical identities were established by application of NMR spectroscopic methods including 2D-NMR, as well as UV and ESI-MS analyses. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: Miconia cabucu; Melastomataceae; flavonoids; flavone dimer